P53 expression in invasive pancreatic adenocarcinoma and precursor lesions - Norfadzilah, M.Y.; Pailoor, Jayalakshmi; Retneswari, M.; Chinna, K.; Noor, L.M. (College of Pathologists, Academy of Medicine Malaysia, 2011)
Patients with pancreatic adenocarcinoma are known to have a high mortality rate. The 5-year survival rate still remains low even now compared to that of the 1960's despite new advances in management including surgery, chemotherapy, pathological classification and molecular diagnostic technologies. Precursors to invasive pancreatic adenocarcinoma have been identified in the last ten years that include mucinous cystic neoplasm, intraductal papillary mucinous neoplasm and pancreatic intraepithelial neoplasia. p53 protein accumulation in the nuclei is a common molecular event in most human neoplasms. Our objective is to investigate p53 expression in pancreatic adenocarcinoma and precursor lesions and their significance. The selected study material encompassed 31 invasive ductal adenocarcinoma, 15 mucinous cystic neoplasm and papillary mucinous neoplasm, and 27 cases of pancreatic intraepithelial neoplasia including grade 1, 2 and 3. Immunoscore was given for each case based on intensity of staining and percentage of cells positive and compared between precursor lesions and invasive adenocarcinoma. A score of 50 and above was considered significant. The results showed that p53 expression increased progressively and significantly with the grade of pancreatic intraepithelial neoplasia and adenocarcinoma (p-value < 0.001). These findings support the concept of multistep carcinogenesis in pancreatic adenocarcinoma and suggest that p53 inactivation occurs in the progression of precursors to pancreatic adenocarcinoma.